2004
DOI: 10.1021/ja0499748
|View full text |Cite
|
Sign up to set email alerts
|

(P)-Helicene Displays Chiral Selection in Binding to Z-DNA

Abstract: Enantiomeric helicenes of (P)-A and (M)-A were synthesized. The binding of the helicenes to B- and Z-DNA was studied quantitatively by CD, equilibrium dialysis, and fluorescence spectroscopy. Enantiomeric (P)-A not only bound selectively to Z-DNA but also effectively converted the B-DNA conformation to Z-DNA. The enantioselectivity of the helicenes offers a new route for the rational design of inhibitors of biological functions that may depend on Z-DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(106 citation statements)
references
References 15 publications
0
105
0
1
Order By: Relevance
“…The supramolecular association of chiral C 2 -symmetrical 180 with DNA revealed that the (P)-enantiomer of 180 displays chiral selection for binding Z-DNA over B-DNA [98]. The corresponding binding constants were found to be (8.0 ± 0.5) × 10 4 M −1 and (1.4 ± 0.3) × 10 4 M −1 for Z-and B-DNA, as measured by fluorescence titration.…”
Section: Helicene-based Chiral Recognition Involving Biologically Relmentioning
confidence: 93%
See 3 more Smart Citations
“…The supramolecular association of chiral C 2 -symmetrical 180 with DNA revealed that the (P)-enantiomer of 180 displays chiral selection for binding Z-DNA over B-DNA [98]. The corresponding binding constants were found to be (8.0 ± 0.5) × 10 4 M −1 and (1.4 ± 0.3) × 10 4 M −1 for Z-and B-DNA, as measured by fluorescence titration.…”
Section: Helicene-based Chiral Recognition Involving Biologically Relmentioning
confidence: 93%
“…Tanaka et al synthesized bis(hydroxymethyl)thia [7]helicene 174 to study its further synthetic chemistry and corresponding applications in the chirality recognition of biological molecules [97][98][99][100]. Hence, the helicene 174 was synthesized in a total of nine steps with an overall 33% yield, where the photochemical cyclization of alkene 175 was a key step to give silyl group protected rac-176.…”
Section: Helicene-based Chiral Recognition Involving Biologically Relmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, redox states of helicenes are practically unknown [33,34]. Assembly of helicenes on surfaces, their uses as liquid crystals, chiral sensors, ligands or additives for asymmetric synthesis and helicene-biomolecule interactions are in the exploratory stages [35][36][37][38][39][40][41][42][43].…”
Section: Helicenesmentioning
confidence: 99%